IPA-Based Simulation in Vocational Business English: Interactive Toolkit Development - Rika Wahyuni Tambunan; Betharia br Sembiring Pandia; Anni Alvionita Simanjuntak; Mujiono Mujiono; Hindra Kurniawan (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Vocational students are expected to develop communication skills that meet workplace demands; however, Business English instruction often remains focused on theoretical content and routine language exercises. This condition limits opportunities for authentic communication practice and affects students’ confidence and performance in professional settings. This study developed and evaluated a simulation-based learning toolkit using a Research and Development approach with the ADDIE framework. The toolkit was designed to support three communication modes through structured learning activities and was implemented with 30 vocational students enrolled in a Business English course. Data were collected through performance-based pretests and posttests, classroom observations, and student reflections. Quantitative data were analysed using paired-sample t-tests, while qualitative findings were used to support the interpretation of learning outcomes. The findings revealed significant improvements in students’ communication performance after the intervention. Students demonstrated better comprehension of workplace texts, more active participation in discussions, and greater confidence in presenting ideas during business meeting simulations. Statistical analysis showed significant differences between pretest and posttest scores across all communication modes (p < 0.001), accompanied by large effect sizes. Students also reported positive perceptions of the learning experience and the relevance of the activities to professional communication contexts. The integration of simulation activities, performance-based assessment, and systematic instructional design effectively enhanced communication competence among vocational learners and strengthened the connection between classroom learning and workplace communication practices